Enantioconvergent Cross‐Couplings of Alkyl Electrophiles: The Catalytic Asymmetric Synthesis of Organosilanes. (5th February 2019) - Schwarzwalder, Gregg M.; Matier, Carson D.; Fu, Gregory C.
Abstract: Metal‐catalyzed enantioconvergent cross‐coupling reactions of alkyl electrophiles are emerging as a powerful tool in asymmetric synthesis. To date, high enantioselectivity has been limited to couplings of electrophiles that bear a directing group or a proximal p/π orbital. Herein, we demonstrate for the first time that enantioconvergent cross‐couplings can be achieved with electrophiles that lack such features; specifically, we establish that a chiral nickel catalyst can accomplish Negishi reactions of racemic α‐halosilanes with alkylzinc reagents with good enantioselectivity under simple and mild conditions, thereby providing access to enantioenriched organosilanes, an important class of target molecules. Abstract : Enantiokonvergente Kreuzkupplungen mit Elektrophilen, denen eine dirigierende Gruppe oder ein benachbartes p/π‐Orbital fehlt, gelangen erstmals. Ein chiraler Nickel‐Komplex katalysiert enantioselektive Negishi‐Reaktionen racemischer α‐Halogensilane mit Alkylzink‐Reagentien unter milden Bedingungen und ermöglicht so die Synthese enantiomerenangereichter Organosilane.